From the sea to the city: explaining gulls’ use of urban habitats - Goumas, Madeleine; Berkin, Charlotte R.; Rayner, Charlie W.; Boogert, Neeltje J. (Frontiers in Ecology and Evolution, 2024)
The expansion of urban areas affects wild animals in a variety of ways. Why members of closely-related species respond differently to urbanisation is often unclear, but an understanding of the factors that lead to urban habitat use or avoidance will have important implications for conservation. Previous research has suggested that urban habitats could favour larger-brained, behaviourally flexible species, which can more readily cope with the novel challenges imposed by urbanisation. However, the opportunity species have to colonise urban areas, and similarities between urban areas and species’ natural habitats, may also explain urban habitat use. We use phylogenetic path analysis to investigate factors that could promote urban breeding and foraging in the gull subfamily, a group with several urbanised species. While we find little evidence to support a relationship between brain size and urban foraging, we reveal an indirect relationship between brain size and urban breeding: cliff-nesting species have relatively larger brains and these species are more likely to breed in urban areas. We show that cliff nesting in gulls is a derived trait and may therefore reflect plasticity in breeding habitat choice, facilitating the use of buildings as nesting sites. Finally, we show that urbanised gull species are less likely to be of international conservation concern or decreasing in population size, exposing the need for more research on the causes and consequences of urban habitat use.